2016
DOI: 10.1038/srep20432
|View full text |Cite
|
Sign up to set email alerts
|

Stroke prevention in atrial fibrillation and ‘real world’ adherence to guidelines in the Balkan Region: The BALKAN-AF Survey

Abstract: Data on the management of atrial fibrillation (AF) in the Balkan Region are limited. The Serbian AF Association (SAFA) prospectively investigated contemporary ‘real-world’ AF management in clinical practice in Albania, Bosnia&Herzegovina, Bulgaria, Croatia, Montenegro, Romania and Serbia through a 14-week (December 2014-February 2015) prospective, multicentre survey of consecutive AF patients. We report the results pertinent to stroke prevention strategies. Of 2712 enrolled patients, 2663 (98.2%) with complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 25 publications
(40 reference statements)
3
59
1
1
Order By: Relevance
“…Oral anticoagulant agents are the mainstay of therapy in secondary prevention. Although numerous oral non-vitamin K antagonists have been developed in recent years, they have not yet replaced warfarin (vitamin K antagonist) (4,5). The efficacy of warfarin treatment is related to many variables such as socio-demographics, genetics, the pharmacokinetics of the drug, and patient adherence to the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Oral anticoagulant agents are the mainstay of therapy in secondary prevention. Although numerous oral non-vitamin K antagonists have been developed in recent years, they have not yet replaced warfarin (vitamin K antagonist) (4,5). The efficacy of warfarin treatment is related to many variables such as socio-demographics, genetics, the pharmacokinetics of the drug, and patient adherence to the therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The survey was conducted in 7 countries in the Balkan region (ie in Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Montenegro, Romania and Serbia) comprising approximately 40 million inhabitants. The survey was designed and conducted by the Serbian Atrial Fibrillation Association (SAFA), a nonprofit multidisciplinary association of expert physicians involved in AF management and research, and the BALKAN‐AF study protocol has been previously reported in detail …”
Section: Methodsmentioning
confidence: 99%
“…The survey was designed and conducted by the Serbian Atrial Fibrillation Association (SAFA), a nonprofit multidisciplinary association of expert physicians involved in AF management and research, and the BALKAN-AF study protocol has been previously reported in detail. 5 The study has been announced to the National Cardiology Societies/relevant Working Groups in Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Former Yugoslav Republic Macedonia, Montenegro, Romania, Serbia and Slovenia. In the participating countries, the study has been approved by the National and/or local Institutional Review Board and, as per local requirements, a signed patient informed consent has been obtained before enrolment.…”
Section: Study Design and Patient Selectionmentioning
confidence: 99%
“…Recent guidelines are preferring use of Rivaroxaban over warfarin 14,15 and this strategy is implemented although at a modest level in a number of countries 16 . In our study the number of patients on Rivaroxaban was very low probably because of the common documented barriers like concerns of bleeding 17 and some others reasons like cost to translate guidelines recommendations into clinical practice 18 .…”
Section: Discussionmentioning
confidence: 99%